2006
DOI: 10.1097/01.ajp.0000148625.84874.48
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Momentary Assessment in Chronic Pain II: Pain and Psychological Pain Responses as Predictors of Pain Disability

Abstract: The psychological prediction of chronic pain disorder disability was determined beyond that accounted for by pain intensity. Nonetheless, psychological functioning explained substantial variance in chronic pain disorder disability. The psychological prediction of immobility and physical impairment was stronger with longer pain duration. Patient characteristics and momentary states of disability-and in particular of immobility-should be carefully distinguished and accounted for in chronic pain disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 65 publications
0
22
0
1
Order By: Relevance
“…[20][21][22] Excessive avoidance can lead to decreased musculoskeletal functioning and physical deconditioning, resulting in more intense pain upon movement. 19 Another interesting finding of this study was that patients who reported pain as more central to their life experienced higher levels of psychological distress. Psychological distress is considered to be one of the most important indicators of adjustment to pain.…”
Section: Discussionmentioning
confidence: 67%
“…[20][21][22] Excessive avoidance can lead to decreased musculoskeletal functioning and physical deconditioning, resulting in more intense pain upon movement. 19 Another interesting finding of this study was that patients who reported pain as more central to their life experienced higher levels of psychological distress. Psychological distress is considered to be one of the most important indicators of adjustment to pain.…”
Section: Discussionmentioning
confidence: 67%
“…The monitoring feature of ODA is based on the electronic diary method of experience sampling [2,3] or ecological momentary assessment [4-6], employed in health psychology research [7-9] to reliably measure symptoms [10-12], momentary mood [13], or other fluctuating states in near real-time. PDAs are programmed to produce randomized calls, which prompt participants to answer diary items with the PDA keyboard or soft-touch screen.…”
Section: Introductionmentioning
confidence: 99%
“…2 Online monitoring is grafted on the Experience Sampling Method (ESM) 18,19 or Ecological Momentary Assessment (EMA), 21,24 which is used to measure fluctuating states, behaviors, and cognitions reliably in real life. 25,26 In ESM/EMA, participants are prompted at random moments to complete an electronic diary.…”
Section: Online Digital Assistancementioning
confidence: 99%
“…The ODA monitoring feature builds on previous experience with electronic diaries in migraine and chronic pain and was used to support the timely detection of attack precursors (the first goal of BT). [16][17][18] The ODA coaching feature was grafted on the possibility of collecting electronic diaries wirelessly and safely directly upon completion, and return advice through the Internet that was tailored to the patient's momentary state. The latter was employed to reinforce preventive actions against attack occurrence (the second BT goal).…”
mentioning
confidence: 99%